POTENSI CIGARETTE SMOKE CONDENSATE TERHADAP PENINGKATAN PEMBENTUKAN BIOFILM CANDIDA albicans ISOLAT ATCC 10261 - Basri A.Gani; Annisa Qashdina Alghassani; Zaki Mubarak; Endang Winiati Bachtiar; Boy M.Bachtiar (Journal of Syiah Kuala Dentistry Society, 2017)
Candida albicans (C. albicans) is the main agent in pathogenesis of oral candidiasis, and also the cigarette smoke is one of predisposing factors of C. Albicans virulence, mainly in biofilm formation that it the role as the initiator of adhesiononoral mucosal. This research aimed to identify the effect of Cigarette smoke condensate (CSC) on biofilm formation of C. albicans. Candida albicans was sensitized with CSC kretek and non-kretek that shown the increase of biofilm formation (p0,05) compared control, specifically in 24 hour. Its related with massa of biofilm formation that seem by microscope (400x) and also CSC non kretek better than CSC kretek in biofilm formation of C. albicans, mainly in 24 and 48 hours, that provisional, in 12 hours were the most dominant biofilm figuration of C. albicans sensitized by CSC kretek, although it intensity is lower than 24 hours. The research was concluded that CSC can be trigger to enhancement of biofilm formation of C. albicans in 24 hours and also CSC non kretek better than CSC kretek.Keyword: Candida albicans, Cigarrete smoke condensate, Biofilm